Customer Loyalty as a Mediating Mechanism between Service Environment and Revisit Intention among Generation Z Café Consumers - Pontillo, Valerie Anne Rose Q.; Acebes, Desiree Mae I.; Bongon, Rochille Janmae D.; Magdayo, Janna Michelle C.; Alas, Brigida Q.; Gomez, Ma. Desiree C.; Castillo, Rhoy F.; Mariquit, Claire Joy C.; Pontillo, Heslie Ree P. (International Review of Management and Marketing, 2026)
Customer loyalty has become a central strategic asset in contemporary hospitality settings, as organizations increasingly recognize that sustained patronage depends not only on immediate satisfaction but on enduring relational commitment. Despite extensive research linking service environment to revisit intention, the mechanisms through which environmental evaluations foster loyalty and subsequently translate into repeat patronage remain underexplored, particularly among Generation Z consumers in emerging urban contexts. Grounded in the Stimulus–Organism–Response framework and servicescape theory, this study examines the mediating role of customer loyalty as the relational mechanism linking service environment and revisit intention among Generation Z café consumers in Iligan City, Philippines. A quantitative research design was employed, with data collected from 500 Generation Z consumers who had actual dine-in experiences in selected cafés. Partial Least Squares Structural Equation Modeling was utilized to evaluate the measurement and structural models, given its suitability for predictive, mediation-oriented research involving latent constructs. The findings indicate that the service environment strengthens revisit intention both directly and indirectly through customer loyalty. Notably, customer loyalty serves as a meaningful mediating mechanism that translates favorable environmental evaluations into sustained revisit intentions. These results underscore that experiential design alone is insufficient unless it cultivates relational commitment. By strategically integrating holistic servicescape planning with loyalty-building initiatives, café operators can enhance customer retention and strengthen long-term competitive positioning among experience-driven Generation Z consumers.